Effects of nanoadditives on emission characteristics of engine fuelled with biodiesel. Issue 1 (2nd January 2020) - Manigandan, S.; Gunasekar, P.; Nithya, S.; Devipriya, J.
ABSTRACT: In this study, the corn blend biodiesel was mixed with titanium dioxide and Zinc oxide along with pentanol to examine their positive effects on a diesel engine. Five percent of ZnO and 5% of TiO2 are added to the corn vegetable oil methyl ester to increase the efficiency of the engine. In addition to the nanoparticles, 2% of pentanol and 1% of nonionic surfactants Span80 are mixed with corn oil. The test fuels are Diesel, CVOME, CVOMEZ50, CVOMEZ100, CVOMET50, and CVOMET100. The properties like density, viscosity, cetane number, pour point, cloud point, calorific value are positively affected due to the addition of nanoparticles in the biodiesel blends. All fuels are tested in a water-cooled diesel engine with the advanced timing of 23°bTDC. The emission like CO, HC, and NOx are dropped 26%, 37%, and 19%, respectively, due to the addition of ZnO and TiO2 . The emission is reduced owing to the high oxygen content in the biodiesel blends compared to diesel. Further 10% reduction is witnessed in soot compared to diesel.